Identificación de los fitoconstituyentes en hojas y tallos de la especie eupathorium triplinerve “asmachilca” - Carlos Torres, Juan Eduardo (2008)
The present work of investigation of descriptive type, was made in the laboratory of Farmacognosia, the faculty of Pharmacy and Biochemistry of the National University of Trujillo – La Libertad, during the months of December to 2006 - March of 2007, in order to identify the fitoconstituyentes in the leaves and stems of Eupathorium triplinerve "Asmachilca". The investigation has been made with the preliminary fitoquímica march of the Dra. Olga Lock, being used a dry and ground sample of the plant in study, which was used reliable of increasing polarity, taking place later the qualitative determination of the fitoconstituyentes by means of the coloration reactions and precipitation, obtaining itself therefore the following fitoconstituyentes: Steroids, tannins, flavonoides, leucoantocianidinas and saponinas